The Correlation Between Mother’s Knowledge About The Impact of The Covid 19 Pandemic and Mother’s Attitudes Toward Bringing Babies to Immunization - Debi Novita Siregar; Pintaken Sembiring Pandia; Ayu Lestari Tarigan; Lia Mauliar Sapitri; Subang Aini Nasution (Caring: Indonesian Journal of Nursing Science, 2022)
The COVID-19 pandemic is a coronavirus pandemic that was first identified in December 2019 in Wuhan, China. Indonesia confirmed the first case of COVID-19 on March 2nd, 2020. The emergence of coronavirus impacted the mother to bring her baby to do immunization. Because the mother was worried about being infected by covid, on the other hand, babies must receive immunization to keep their immune systems. This study aimed to know the correlation between maternal knowledge about the impact of the Covid 19 pandemic and maternal attitudes in bringing babies to immunization at Sirapit Public Health Center. This study is quantitative research and uses a cross-sectional approach with a chi-square test. For acquiring samples, this study uses an accidental sampling technique. Of 40 respondents, five had poor knowledge (12.5%), no positive attitude (0%), and five with a negative attitude. Another 24 respondents (60%) had decent knowledge, 21 respondents with a positive attitude (67.7%), and three respondents with a negative attitude (33.3%). Lastly, 11 respondents had good knowledge (27.5%), ten respondents with a positive attitude (32.2%), and one respondent with a negative attitude (11.1%). Chi-square statistical test showed p-value = 0.000 (p-value<0.05). Â